Soil physical properties and organic carbon under no tillage compared with natural forest, in an inceptisol (Revista de Ciências Agroveterinárias, 2010)
The soil physical quality is related with its use and management and with the soil organic carbon content. This work was carried out aiming to evaluate the effect of no-tillage adoption period with onion and tobacco, compared to the natural forest, on soil global density, porosity, water content, water stability of aggregate, resistance to the penetration, organic carbon content and water infiltration rate. The study was conducted in 2007, in the city of Ituporanga, Santa Catarina State, southern Brazil. Areas under no-tillage management during five, two e one year old, and a natural forest area, were assessed in an INCEPTISOL soil. The type of agricultural soil use changed soil physical properties, when compared to the natural forest. The soil water infiltration rate was more affected by the kind of soil use than other soil physical properties, with values of 72 mm h-1 in the forest and 2 mm h-1 to 8 mm h-1 in the cropped lands. The soil conventional tillage adopted before no-tillage, and the duration time of soil no-tillage, influenced soil porosity, stability of aggregate, resistance to the penetration and water infiltration initial rate. The soil resistance to penetration and soil density presented inverse relationship with the soil organic matter content.
Keywords: Soil physics; Soil porosity; Soil water infiltration.